Food Supplements Containing Botanicals: Benefits, Side Effects and Regulatory Aspects The Scientific Inheritance of the EU Project PlantLIBRA (Springer International Publishing, 2018)
This book provides a detailed analysis of the scientific, technical and regulatory aspects of plant food supplements designed for integration into the normal diet. Each contributor is involved in the European Plant LIBRA project, and the chapters summarize the results of the project while integrating further research on botanical supplements. With its focus on the epidemiology, risk assessment and evidence based approaches, this text presents a unique and comprehensive overview of botanical food supplements, from their production and chemistry to their side effects and regulatory aspects. Food Supplements Containing Botanicals: Benefits, Side Effects and Regulatory Aspects begins by outlining the general aspects of food supplements, before examining quality and risk assessment of food supplements with botanicals. The following chapters focus on sources, models and human studies which support health claims for these supplements, followed by chapters outlining side effects and potential causes for concern. The issue of increasing consumer expectations is also explored, with methods for meeting these expectations provided. In presenting this well-rounded and up-to-date collection of information on botanical supplements, this book is of great importance to food industry professionals working with botanical supplements.